Pengaruh Profitabilitas dan Likuiditas terhadap Penerimaan Opini Audit Going Concern - Maya Indriastuti (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2016)
Going concern audit opinion received by a company indicates the conditions and events which raise doubt auditor will be survival of the company. This study aims to obtain empirical evidence about the extent of influence the profitability and liquidity of the going-concern audit opinion. The sample in this research as many as 54 companies listed in Indonesia Stock Exchange in 2013-2014. The data will be analyzed by using logistic regression analysis. The results showed that the profitability and liquidity have a significant negative effect on the going concern audit opinion